2022
DOI: 10.3390/su141811667
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-Based Fault Prediction for Real-Time Monitoring of Sensor Data in Hospital Environment Using Machine Learning

Abstract: The amount of data captured is expanding day by day which leads to the need for a monitoring system that helps in decision making. Current technologies such as cloud, machine learning (ML) and Internet of Things (IoT) provide a better solution for monitoring automation systems efficiently. In this paper, a prediction model that monitors real-time data of sensor nodes in a clinical environment using a machine learning algorithm is proposed. An IoT-based smart hospital environment has been developed that control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Faults can be classified into a gain fault, stuck-at-fault, offset fault, and out-ofbounds fault. Uppal et al [71] developed a different machine learning model to predict the faults in real-time sensor data monitoring in the hospital environment. The result analysis shows that the machine learning modes applied over IoT-based sensors are proficient in monitoring the automation process of the hospital process.…”
Section: Fault Detectionmentioning
confidence: 99%
“…Faults can be classified into a gain fault, stuck-at-fault, offset fault, and out-ofbounds fault. Uppal et al [71] developed a different machine learning model to predict the faults in real-time sensor data monitoring in the hospital environment. The result analysis shows that the machine learning modes applied over IoT-based sensors are proficient in monitoring the automation process of the hospital process.…”
Section: Fault Detectionmentioning
confidence: 99%
“…They gathered the related data from the process and equipment sensors of centrifugal pumps to generate fault prediction alerts properly in decision support systems for operatives. In another study [70], the authors reported a fault prediction model with the aim of real-time tracking of sensor data in an IoT-enabled cloud environment for a hospital by machine learning. They applied the DT, KNN, NB, and RF techniques for controlling unanticipated losses produced by different faults.…”
Section: Machine Learning-based Fault Predictionmentioning
confidence: 99%
“…Screen time has a clear connection with high blood pressure irrespective of the physique of any human. Hindering passive sitting with computer use (light walking or basic exercises) may effectively lessen blood pressure [ 75 , 76 ].…”
Section: Proposed Modelmentioning
confidence: 99%